Albania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The study first examines Albania's projected debt dynamics for the period 2001-10 and then describes the present public debt situation. The paper also provides a simulation of debt dynamics under macroeconomic conditions. The sensitivity of debt dynamics is also tested. The key features and financial stability of the Albanian pension scheme are also discussed. The following statistical data are included in detail: basic indicators, consumer price subsidies, agricultural production, population, labor force, employment, fiscal accounts, tax revenue shares, exchange rate, monetary survey, balance of payments, and so on.